Equity research netflix, inc - Hilke, Fabian Louis Jonas (2022)
This Equity Research WP focuses on the American streaming service Netflix. The task is to find out whether the share price is justified in a 12-month preview. Based on this, a recommendation is formulated to buy, hold or sell the stock. The share price was analyzed using a Discounted Cash Flow method and a relative multiple method with peer companies. In addition, company-specific information such as turnover or costs had to be forecasted, but also various macroeconomic factors had to be taken into account. Particular attention had to be paid to the 4 core regions Netflix is operating in.